THE EFFECT OF LIQUIDITY, COMPANY SIZE, AND INDEPENDENT COMMISSIONER ON TAX AGGRESSIVENESS - Athifah, Lydia Nur; Mahpudin, Endang (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.10.NO.02.TAHUN. 2021DO - 10.24843/EEB.2021.v10.i02.p01, 2021)
The purpose of this study was to determine the effect of liquidity, company size, and independent commissioners on tax aggressiveness. This research was conducted at the food and beverage sub-sector consumer goods companies in the period 2014-2018. The data analysis technique used is the linear regression test. Based on the research results, it is known that partially liquidity does not significantly influence tax aggressiveness, company size significantly influences tax aggressiveness, and independent commissioners do not significantly influence tax aggressiveness, and simultaneously independent variables such as liquidity, company size, and commissioners The independent variables jointly influence the dependent variable, namely tax aggressiveness. Keywords : Liquidity; Company Size; and Independent Commissioner